Effect of supplementary concentrate on growth and carcass characteristics in crossbred sheep of dual purpose - SINGH, N P; SANKHYAN, S K; PRASAD, V S S (The Indian Journal of Animal Sciences, 2014)
An investigation was conducted to study the live weight gains, carcass characteristics and meat quality of the male and female lambs of a dual-purpose breed. Lambs (40) were completely weaned at 75 days of age and divided into 1-5 groups. All the lambs were grazed together on a 3 years old Cenchrus ciliaris grass pasture for 194 days. Lambs of group 1 were supplemented with ad lib. concentrate mixture, and those of the 2, 3 and 4 groups, respectively, received 75%, 50% and 25% of the ad lib. supplementation. The lambs of group 5, with no supplementation acted as control. The daily concentrate allowance and weekly body weights were recorded. These lambs were slaughtered at the age of 269 days, and their carcass and meat quality traits recorded. The over all growth rate of 67±4.6 g in the control group 5 improved to 123±7.2 g/head/day in the ad lib. concentrate supplemented group 1 through 87±6.8, 104±9.7 and 119±5.9 g in the groups 4, 3 and 2 respectively. The slaughter weights, empty live' weights, hot carcass weights, dressing percentage, join eye area and back fat thickness of the slaughtered lambs linearly and significantly improved with the increaSing levels of concentrate supplementation. However, the rate of increase slowed down beyond 300g/head/day concentrate supplementation. Most desirably the edible offals content increased and the inedible offal content decreased with the increasing amount of supplementation. The dressed carcass decreased and the total fat content increased with the increasing levels of supplementation, but undesirably to the extent of rendering the carcasses obtained from the lambs supplemented with higher levels unsuitable from meat quality point of view. It was concluded that although the live weights of the lambs increased with the gradual increase in the level of concentrate supplementation, the higher levels resulted in higher deposition of fat and, therefore, the concentrate supplementation @300 g/head/day in addition to grazing was most sufficient and appropriate to obtain desired quantity and quality of the dressed carcasses from the lambs of the fine wool sheep.